Effectiveness of E-Court-Based Services in Resolving Civil Cases at the Sukadana District Court - Iqbal Juliansyah; Imam Mustofa; Moelki Fahmi Ardliansyah (Istinbath : Jurnal Hukum, 2024)
This study examines the implementation of the effectiveness of E-Court-based services at the Sukadana District Court in an effort to resolve various civil issues. E-Court as an innovation of information technology in the judicial system aims to accelerate, simplify, and increase the transparency of the judicial process. This service includes electronic registration of lawsuits, payment of court fees, submission of documents, implementation of trials to delivery of decisions digitally. This study aims to determine the effectiveness of E-Court-based services in resolving civil issues at the Sukadana District Court. The research method used is qualitative using an empirical legal approach involving data collection through in-depth interviews and document analysis, using triangulation techniques to determine interview sources including the chief justice, deputy chief justice, clerk, judges, staff, advocates and the public in litigation. Evaluation of the success of E-Court at the Sukadana District Court shows several determining factors for success, such as reliable technological infrastructure, commitment to implementing regulations and positive acceptance from service users. This study found that the implementation of E-Court was able to reduce bureaucracy, accelerate the judicial process and provide wider and more transparent access for the parties to the case. However, challenges such as technological infrastructure and human resource readiness still need to be overcome to achieve optimal implementation. Overall, E-Court has the potential to be an effective solution in resolving civil issues at the Sukadana District Court, as well as a step forward in modernizing the justice system in Indonesia. This study also revealed that E-Court has positive implications, such as increasing the effectiveness of case resolution, saving time and costs, and increasing transparency and integrity of the justice system.